From Gurudev to Doctor-Sahib - Heifetz, Daniel Philip (Method & theory in the study of religion, 2018)
The All World Gayatri Pariwar is a modern Hindu movement working to revive ancient Vedic-style rituals. The movement was founded by a charismatic figure named Shriram Sharma, but is now headed by his successor, a medical doctor named Pranav Pandya. I argue that the continued vitality of the movement in the absence of its charismatic founder has to do with the ways in which Pandya’s scientific authority as a medical doctor replaces Sharma’s charismatic authority. By attending to the affective dimensions of these two forms of authority, their differences become less stark and it becomes clear how scientific authority, despite its seeming disenchantment, might retain some of the emotional power of charismatic authority.